2017
DOI: 10.1186/s13104-017-3023-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and intensity of Schistosoma mansoni infections among schoolchildren attending primary schools in an urban setting in Southwest, Ethiopia

Abstract: ObjectiveTo determined both prevalence and intensity of Schistosoma mansoni infections among schoolchildren attending primary schools in Jimma town, an urban setting, Southwest, Ethiopia.ResultsThe prevalence of S. mansoni infections was 8.4%. S. mansoni infections were found in all 17 schools, but the school prevalence ranged from 1.7 to 26.7%. This variation in prevalence could be explained by the proximity of the schools to the river crossing the town and water bodies near the schools. Boys were more infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
6
12
0
Order By: Relevance
“…Regionally, the occurrence of urogenital and intestinal parasites influence by multiple elements including the environmental factors and geographic location, which can make a person at higher risk for particular parasites or indirectly affect the parasite survival, distribution, and transmission [ 1 , 23 , 35 , 39 ]. In this study, S. haematobium , S. mansoni , H. nana , Cryptosporidium spp., and E. histolytica compromised the identified parasites, with considerably higher prevalences in diabetic individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regionally, the occurrence of urogenital and intestinal parasites influence by multiple elements including the environmental factors and geographic location, which can make a person at higher risk for particular parasites or indirectly affect the parasite survival, distribution, and transmission [ 1 , 23 , 35 , 39 ]. In this study, S. haematobium , S. mansoni , H. nana , Cryptosporidium spp., and E. histolytica compromised the identified parasites, with considerably higher prevalences in diabetic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rural areas of Kosti locality suffer from infrastructures and health serves deficiency, in addition to the lack of the proper source of water supply, which could reflect the higher prevalence of diseases in a rural area compared to urban regions. Previously, several studies were stated a high positivity rate for urogenital schistosomiasis and IPIs in males [ 2 , 3 , 23 ]. Unlike our study, Tangi FB et al study [ 39 ] found a high frequency of IPIs among females in both diabetes mellitus and control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schistosomiasis has a widespread distribution in several parts of Ethiopia usually at an altitude between 1200-2000 m above sea level [6], where an estimated 38.3 million people are living in schistosomiasis endemic areas [7]. In endemic areas, children have a greater risk of becoming infected as well as re-infected [8][9][10]. Fascioliasis is another important parasitic snail-borne disease in tropical and subtropical countries [11].…”
mentioning
confidence: 99%
“…The selected studies confirm that schistosomiasis is or was prevalent in peri-urban and urban areas in the countries assessed. Point prevalence estimates ranged from low (below 1% in Tanga, Tanzania [ 13 ]; 1.9% in Korhogo, Côte d’Ivoire, 2015 [ 28 ]; 8.4% in Jimma Town, Ethiopia [ 29 ]) to moderate (17.4% in Ibadan, Nigeria [ 30 ]; 20.7%, Lusaka, Zambia, 2007 [ 31 ]; 24.9%, State of Alagoas, Brazil [ 32 ]) to high (61.5%, Adwa, Ethiopia [ 33 ]; 60.9%, Abeokuta, Nigeria in 1987 [ 34 ]]). Years of data collection have been provided when specifically indicated in the papers.…”
Section: Resultsmentioning
confidence: 99%